A wearable mobility assessment device for total knee replacement: A longitudinal feasibility study. (June 2015) - Kwasnicki, Richard M.; Ali, Raza; Jordan, Stevan J.; Atallah, Louis; Leong, Julian J.H.; Jones, Gareth G.; Cobb, Justin; Yang, Guang Zhong; Darzi, Ara
Abstract: Background: Total knee replacement currently lacks robust indications and objective follow-up metrics. Patients and healthcare staff are under-equipped to optimise outcomes. This study aims to investigate the feasibility of using an ear-worn motion sensor (e-AR, Imperial College London) to conduct objective, home-based mobility assessments in the peri-operative setting. Methods: Fourteen patients on the waiting list for knee replacement, and 15 healthy subjects, were recruited. Pre-operatively, and at 1, 3, 6, 12 and 24 weeks post-operatively, patients underwent functional mobility testing (Timed Up and Go), knee examination (including range of motion), and an activity protocol whilst wearing the e-AR sensor. Features extracted from sensor motion data were used to assess patient performance and predict patients' recovery phase. Results: Sensor-derived peri-operative mobility trends correlated with clinical measures in several activities, allowing functional recovery of individual subjects to be profiled and compared, including the detection of a complication. Sensor data features enabled classification of subjects into normal, pre-operative and 24-week post-operative groups with 89% (median) accuracy. Classification accuracy was reduced to 69% when including all time intervals. Discussion: This study demonstrates a novel, objective method of assessing peri-operative mobility, which could be used to supplement surgical decision-making and facilitate community-based follow-up. Highlights: TKR currently lacks robust indications and objective follow-up metrics. A motion sensor is used to conduct objective, home-based mobility assessments. Sensor-derived mobility trends correlated with clinical measures. Sensor data features enabled classification of subjects into peri-operative groups.